Description of Mycobacterium pinniadriaticum sp. nov., isolated from a noble pen shell (Pinna nobilis) population in Croatia - Špičić, Silvio; Duvnjak, Sanja; Papić, Bojan; Reil, Irena; Zrnčić, Snježana; Mihaljević, Željko; Naletilić, Šimun; Zupičić, Ivana Giovanna; Kompes, Gordan; Habrun, Boris; Mareković, Ivana; Zdelar-Tuk, Maja (Frontiers in Microbiology, 2023)
Introduction Shortly before the mass mortality event of the noble pen shell (Pinna nobilis) population in the south-eastern Adriatic coast, two rapidly growing Mycobacterium strains CVI_P3T (DSM 114013 T, ATCC TSD-295 T) and CVI_P4 were obtained from the organs of individual mollusks during the regular health status monitoring. Methods The strains were identified as members of the genus Mycobacterium using basic phenotypic characteristics, genus-specific PCR assays targeting the hsp65 and 16S rRNA genes and the commercial hybridization kit GenoType Mycobacterium CM (Hain Lifescience, Germany). MALDI-TOF mass spectrometry did not provide reliable identification using the Bruker Biotyper Database. Results and discussion Genome-wide phylogeny and average nucleotide identity (ANI) values confirmed that the studied strains are clearly differentiated from their closest phylogenetic relative Mycobacterium aromaticivorans and other validly published Mycobacterium species (ANI ≤ 85.0%). The type strain CVI_P3T was further characterized by a polyphasic approach using both phenotypic and genotypic methods. Based on the phenotypic, chemotaxonomic and phylogenetic results, we conclude that strains CVI_P3T and CVI_P4 represent a novel species, for which the name Mycobacterium pinniadriaticum sp. nov. is proposed.